Některé shodné motivy městských legend v Bulharsku a v České republice - Rosina Kokudeva (Studia Ethnologica Pragensia, 2020)
The presented article identifies and compares several shared motifs of urban legends in Bulgaria and the Czech Republic. The legends are classified into following thematic groups: 1) mysterious narratives and encounters with preternatural creatures, which are neither helpful nor harmful; 2) mysterious signs and encounters with preternatural creatures which cause death or other harm to the participants of the story; 3) mysterious signs and encounters with preternatural creatures which help people; 4) summoning and invoking of ghosts; 5) criminal stories — murders and assaults causing bodily harm with or without motive; 6) scary stories — parodies. Analyzed parallels between particular narratives documented in Bulgaria and the Czech Republic confirm shared folkloric substratum which points out to both their universality and international distribution.